RATIB TOLAK BALA TAREKAT SYADZILIYAH DI KECAMATAN NA IX-X KABUPATEN LABUHANBATU UTARA: ANALISIS SURAH AT-THAGHABUN AYAT 11 DAN AL-HADID AYAT 22 - Ritonga, Abdul Rahman; Hasyimsyah Nasution (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The meaning of disasters for the people of Na IX-X sub-district often experiences misperceptions that assume that disasters are signs of supernatural things that will attack the community such as sacrifices and so on. This is inseparable from the lack of religious knowledge and the weakness of the Na IX-X sub-district community in the field of science. In fact, the disaster that occurred can be explained by science. This is where it is important for the community to reflect on the power of Allah SWT that everything happens because of Allah's permission and disasters as a form of love and a test from Allah SWT. Getting Allah's love so that disasters and punishments can be asked to be kept away by Allah SWT. The purpose of the study was to increase positive changes in the community in terms of physical and piety. The quality of peace of mind during a disaster and religious psychology towards religious teachings greatly influence the desired end result. The research method used is qualitative descriptive tahlili, data obtained through interviews, documentation and literature studies of related verses are then processed into a manuscript. The theory used is the theory of monistic religious psychology proposed by William James. This theory suggests that religious experience is the result of the integration of thoughts, feelings and desires and the role of religion in influencing human psychology. The results of this study indicate that the ratib tolak bala is very related to the values ​​of Surah At-Thaghabun verse 11 and Al-Hadid verse 22, namely disaster as a test, an eraser of sins and a means of getting close to Allah.